Difference of gut microbiota between patients with negative and positive HBeAg in chronic hepatitis B and the effect of tenofovir alafenamide on intestinal flora - Long, Jianfei; Gong, Jingru; Zhu, Han; Liu, Xiaolin; Li, Ling; Chen, Bicui; Ren, Hongyan; Liu, Chao; Lu, Huiping; Zhang, Jiming; Wang, Bin (Frontiers in Microbiology, 2023)
Background: Severe liver diseases, such as liver fibrosis, cirrhosis, and liver cancer, are mainly caused by hepatitis B virus (HBV). This study investigated the differences between gut microbiota in HBeAgpositive and negative groups of patients with chronic hepatitis B (CHB) and investigated the effect of tenofovir alafenamide (TAF) on gut microbiota. Methods: This prospective study included patients with CHB not taking nucleoside antivirals (No-NAs group, n = 95) and those taking TAF (TAF group, n = 60). We divided CHB patients into two groups according to the HBeAg status of the subjects on the day of data collection. Phase 1 are HBeAgnegative patients and phase 2 are HBeAg-positive patients. Patients were divided into two subgroups according to their e-antigen status. Phase 1 is the HBeAg-negative patient group, and Phase 2 is the HBeAg-positive patient group. We investigated the improvement of clinical symptoms by TAF, as well as differences in gut microbiota between different groups by 16S rRNA high-throughput sequencing.Results: Gut microbiota demonstrated significant differences between patients with HBeAg-positive and -negative CHB. Both the No-NAs and TAF Phase 2 subgroups demonstrated significantly increased microbiota richness and diversity, showing greater heterogeneity. Additionally, the Phase 2 subgroup exhibited a low abundance of pathways associated with glucose metabolism and amino acid metabolism. The TAF group demonstrated a significantly decreased HBV load, alanine aminotransferase, and aspartate aminotransferase and a significant increase in prealbumin compared with the No-NAs group. No significant difference was found in uric acid, creatinine, blood calcium, inorganic phosphorus, eGFR, and β2-microglobulin concentrations between the two groups.Additionally, the urea level in the TAF group was significantly lower than that in the No-NAs group, but with no significant effect on other indicators such as eGFR and β2-microglobulin. Conclusions: This study revealed significant differences in gut microbiota composition and function between patients with HBeAg-positive and -negative CHB. Additionally, in this study, no significant differences in gut microbial community diversity were observed between patients in the No-NAs and TAF groups.this study revealed no significant effect of the use of TAF on gut microbiota diversity.